The organic peroxides instability rating research based on adiabatic calorimetric approaches and fuzzy analytic hierarchy process for inherent safety evaluation. Issue 2 (6th August 2015) - Ni, Lei; Jiang, Juncheng; Wang, Zhirong; Yao, Jun; Song, Yuan; Yu, Yuan
Abstract : This article proposes a new method of instability classification of organic peroxides (ICOP) for assessing the risk of decomposition reaction of organic peroxides, based on the adiabatic calorimetric approaches and fuzzy analytic hierarchy process (FAHP). Tonset is set as instability possibility index. Maximal power density, adiabatic temperature rise, maximum pressure rate, and maximum pressure are set as instability severity index (ISI) with proper weightings by FAHP. Instability possibility index and ISI are converted into ICOP based on risk matrix. The organic peroxides instability can, therefore, be quantified and divided into four levels, acceptable, moderate risk, highly dangerous, and seriously dangerous. Thermal decomposition of di‐tert‐butyl peroxide 25 mass % and tert‐butyl hydroperoxide 68.4 mass % are tested with Vent Sizing Package 2 and Phi‐Tech 1 which has the function of Accelerating Rate Calorimeter, respectively. Thermal decompositions of other organic peroxides are presented from citation. The instability rating results of these organic peroxides are presented to illustrate the validity of the method. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 200–207, 2016